Environmentally relevant levels of BDE-209 induces proteomic and phosphoproteomic reprogramming in murine melanoma cells - Mariana Galvão Ferrarini; Micheli Marchi; Erick Laurent Moggio; Hulyana Brum; Fernanda G. Kugeratski; Michel Batista; Ciro Alberto Oliveira Ribeiro; Andréa Rodrigues Ávila (Chemosphere, 2026)

Amphibian strongholds: protected areas and the future of direct-developing frogs of the genus Ischnocnema in the Atlantic forest under climate change - Rodrigo Barbosa Fontana; Fernanda Thiesen Brum; Camila Both; Sandra Maria Hartz (Biodiversity and Conservation, 2025)

Conservation beyond protected areas: what is known about amphibians in agroforests? - Gabriele Volkmer; Larissa Donida Biasotto; Fernanda Thiesen Brum; Márcio Borges-Martins (Biodiversity and Conservation, 2025)

Multistage treatment system integrating constructed wetlands and microalgae for wastewater reuse and bioenergy recovery - Gustavo S. Colares; Luana T. Junqueira; Fernanda N. Brum; Romualdo J.C. Wanderley; Tainá Conzatti; Lenin D. Garcia; Lucia H.R. Rodrigues; Carlos A. Lutterbeck; Ênio L. Machado; Odorico Konrad (Journal of Water Process Engineering, 2025)

Effects of Metformin Treatment Against Endometrial Cancer Cells Cultured In Vitro or Grafted into Female Balb/C Nude Mice: Insights into Cell Response and IGF-1R and PI3K/AKT/mTOR Signaling Pathways - Vânia Marísia Santos Fortes dos Reis; Franciely Machado Ramos; Henrique Leal de Oliveira; Fernanda Dapper Machado; Sara Hartke; Amanda Machado-Weber; Ariane Germeyer; Thomas Strowitzki; Lúcia Maria Kliemann; Helena von Eye Corleta; Ilma Simoni Brum; Edison Capp; et al. (Cell Biochemistry and Biophysics, 2025)

Similar, but Not the Same: Time and Mode of Climatic Niche Evolution in a Highly Endemic Lineage - Patricia Padilha; Fernanda Thiesen Brum; Renato Mello‐Silva; Isaac Sacramento; Suzana Alcantara (Journal of Biogeography, 2025)
Aim Plant lineages are disproportionally diverse in areas characterised by specific climatic regimes. The campos rupestres habitats in the mountains of Eastern/Central Brazil, for instance, display huge plant endemism and high precipitation seasonality. The genus Vellozia is an emblematic group in there, with most species being endemic and few occurring disjunctively across mountain outcrops of the Neotropics. We aim to test the climate conservatism in the genus, as suggested by its high levels of endemism. Location Neotropic. Taxon Genus Vellozia (Velloziaceae, monocots). Methods We combined MAXENT ecological niche models (ENM) and phylogenetic comparative analyses. Niche overlap between species was estimated based on the environmental similarity and the spatial overlap projected by the ENM. We also traced the climatic niche in the environmental space to describe how its divergence accumulated through time. Results We found varying levels, from 16% to 100%, of species pairs displaying niche overlap across distinct lineages of the genus. When niches overlap, they are more similar than expected by chance and not due to habitat availability, suggesting habitat selection. Niche similarity estimates in both ecological and geographical space did not exhibit conserved phylogenetic signals. There was an expressive disparification in the climatic niches in the last 5 m.y., decoupled from the earlier peaks of lineages diversification. Main Conclusions Contrary to the expected, we found labile and fast evolution of climatic niches, implying that endemisms do not result from climate niche conservatism in Vellozia . The most diverse clade of Vellozia occupies cooler and wetter environments than the ancestral and other extant lineages of the genus. This pattern contrasts with the historical climatic turnover, for example, cooling‐arid vs. warming‐wet periods, established since the Pliocene glacial cycles. Moreover, it also poses additional challenges for this lineage and its associated habitats in the face of the current climate change.

Climate change will threaten endemic frogs in the Araucaria Forest - Pedro de O. Calixto; Felipe W. Pereira; Fernanda T. Brum; Lucas B. Crivellari; Mauricio O. Moura (Biodiversity and Conservation, 2025)

Bees travelling south: Climate‐induced range shifts and suitable habitat losses in south‐eastern neotropics - Felipe W. Pereira; Matheus L. Araujo; Fernanda T. Brum; Gabriel A. R. Melo; Mauricio O. Moura; Rodrigo B. Gonçalves (Journal of Biogeography, 2024)
Aim To provide an assessment of climate change impacts on a set of wild pollinators restricted to one of the regions with the greatest diversity of bees in the world. Also, we aimed to test whether functional groups responded differently to climate projections. Location South‐eastern South America (SES). Taxon Bees (Hymenoptera: Apidae sensu lato). Methods We selected 18 species of bees mostly restricted to the SES region, modelled their distributions and assessed the possible impacts of near future (2050) climate change in species richness and shifts in range centroids. Potential impacts related to different functional groups were evaluated through t ‐tests. Results SES species richness was projected to decrease in the northernmost regions and increase southward. Most bee species were predicted to shift their range centroids towards the south‐west and south, while suitable stable areas were found in southern Brazil. We also found higher proportional losses in suitable areas for eusocial species compared to solitary ones, while generalists showed slightly lower gains than specialists. Main Conclusion SES bees are likely to undergo changes in the near future, with projected losses of species at northern portions and southward increases. The identified stable areas in southern Brazil underscore the importance of conservation efforts in the region, particularly in natural grasslands – an endangered habitat with high bee diversity. Although our results suggest higher vulnerability for functional groups traditionally considered more resilient, it is essential to acknowledge that other factors, including habitat and mutualists availability, behavioural particularities, phenology and range size, must be determinants for the vulnerability of species to ongoing climate change.

How much Araucaria Mixed Forest remains? Novel perspectives on conservation status based on satellite imagery and policy review - Bruna Eliz Zorek; Sumalika Biswas; Fernanda Thiesen Brum; Peter Leimgruber; Marcos Bergmann Carlucci (Biological Conservation, 2024)

Frequencies of micronuclei in buccal cells and their spatial distribution in a population living in proximity to coal mining areas in southern Brazil - Niely Galeão da Rosa Moraes; Alicia da Silva Bonifácio; Fernanda Oliveira Reis; Thais dos Anjos Velho; Paula Florencio Ramires; Rodrigo de Lima Brum; Julia Oliveira Penteado; Flávio Manoel Rodrigues Da Silva Júnior (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2024)

TRPV4 Activation and its Intracellular Modulation Mediated by Kinin Receptors Contribute to Painful Symptoms Induced by Anastrozole - Maria Fernanda Pessano Fialho; Evelyne Silva Brum; Gabriela Becker; Sara Marchesan Oliveira (Molecular Neurobiology, 2024)

Addressing Knowledge Shortfalls in Conservation Science: A long way to go, as quickly as possible - Javier Nori; Bea Maas; Fernanda Brum; Fabricio Villalobos (Biological Conservation, 2023)

Corrigendum to “Minding the gap: Range size and economic use drive functional trait data gaps in the Atlantic Forest” [Biol. Conserv., vol. 283 (2023) 1–7, 110087] - Ana Carolina Petisco-Souza; Fernanda Thiesen Brum; Vinícius Marcilio-Silva; Victor P. Zwiener; Andressa Zanella; Arildo S. Dias; Andrés González-Melo; Steven Jansen; Guilherme G. Mazzochini; Ülo Niinemets; Valério D. Pillar; Enio Sosinski; et al. (Biological Conservation, 2023)

Minding the gap: Range size and economic use drive functional trait data gaps in the Atlantic forest - Ana Carolina Petisco-Souza; Fernanda Thiesen Brum; Vinícius Marcilio-Silva; Victor P. Zwiener; Andressa Zanella; Arildo S. Dias; Andrés González-Melo; Steven Jansen; Guilherme G. Mazzochini; Ülo Niinemets; Valério D. Pillar; Enio Sosinski; et al. (Biological Conservation, 2023)

Photocatalytic degradation of Rhodamine B dye by nanostructured powder systems containing nanoencapsulated curcumin or ascorbic acid and ascorbyl palmitate liposomal - Samanta da Silva Gündel; Fernanda Reis Favarin; Éricles Forrati Machado; Daniel Moro Druzian; Cristiane dos Santos; Luis Fernando Wentz Brum; Aleksandro Schafer da Silva; William Leonardo da Silva; Aline Ferreira Ourique (Environmental Science and Pollution Research, 2023)

Could the fibromyalgia syndrome be triggered or enhanced by COVID-19? - Maria Fernanda Pessano Fialho; Evelyne Silva Brum; Sara Marchesan Oliveira (Inflammopharmacology, 2023)

TRPA1 participation in behavioral impairment induced by chronic corticosterone administration - Gabriele Cheiran Pereira; Elisa Piton; Jéssica Bornholdt; Brenda Moreira dos Santos; Amanda Spring de Almeida; Diéssica Padilha Dalenogare; Maria Fernanda Pessano Fialho; Gabriela Becker; Evelyne da Silva Brum; Tuane Bazanella Sampaio; Sara Marchesan Oliveira; Mauro Schneider Oliveira; et al. (Psychopharmacology, 2023)

Arsenite and arsenate toxicity in the earthworm Eisenia andrei (Bouché 1972) in natural soil and tropical artificial soil - Fernanda Oliveira Reis; Eduarda de Moura Garcia; Lisiane Martins Volcão; Ronan Adler Tavella; Rodrigo de Lima Brum; Larissa Müller; Erico Kunde Correa; Juliane Ventura-Lima; Flavio Manoel Rodrigues da Silva Júnior (Environmental Science and Pollution Research, 2022)

Chemical, antioxidant and cytotoxic profile of hydroalcoholic extracts of plants from Southern Brazil and their activity against pathogenic fungi isolated from dogs and cats with sensitivity and resistance to conventional antifungals - Claudia Giordani; Stefanie Bressan Waller; Isabel Martins Madrid; Karina Affedlt Guterres; Caroline Bohnen de Matos; Jessica Fernanda Hoffmann; Luciana Laitano de Castro; Fábio Clasen Chaves; Renata Osório de Faria; Marlete Brum Cleff (Natural Product Research, 2022)

Multiresistant bacteria isolated from domestic and wild animals with skin lesions were susceptible to native plants from Southern Brazil - Claudia Giordani; Stefanie Bressan Waller; Karina Affeldt Guterres; Cristine Cioato da Silva; Raulene Rodrigues Lobo; Jéssica Fernanda Hoffmann; Soliane Carra Perera; Fábio Clasen Chaves; Sílvia Regina Leal Ladeira; Eliza Simone Viegas Sallis; Gilberto D’Ávila Vargas; Marlete Brum Cleff (Natural Product Research, 2022)

Phylogeography and species delimitation of the Neotropical frog complex (Hylidae: Scinax granulatus ) - Matías M. Malleret; Marcelo D. Freire; Priscila Lemes; Fernanda T. Brum; Arley Camargo; Laura Verrastro (Zoologica Scripta, 2022)
Understanding which factors driving the genetic structure, geographic distribution patterns, and divergence of populations/species are of great interest in ecology and evolutionary biology. Phylogeographic and species hypotheses combined to distribution models may elucidate which phenomena drove evolutionary history of the biota of different biomes and ecoregions. Herein, we used distribution, environmental and genetic data to shed light on the evolutionary diversity of the Scinax granulatus complex, exploring the phylogeographic patterns, genetic structure and species boundaries across the Pampa and Southern Atlantic Forest biomes. We recovered four mitochondrial lineages which correspond to two putative species within the S . granulatus complex. We used genetic data to define species hypothesis with three discovery methods: bGMYC, bPTP and ASAP, and two delimitation approaches: BPP and BPP + gdi. We validated the species boundaries, confirming the differentiation of Scinax sp. lineage D from Atlantic Forest lowlands habitats, based on genetic data, ecological divergence and monophyly. Lineage D exhibited niche differentiation from S . granulatus sensu stricto (s.s.) based on distribution and environmental data. The climatic suitability of S . sp. D is defined by thermal variables, while that of S . granulatus s.s. was associated with rainfall. The diversification of the S . granulatus complex began during the Pliocene, but the colonization and divergence of lineages took place more recently during the Pleistocene. This study strongly suggests species‐level evolutionary divergence among lineages of S . granulatus complex, and highlights the need to carry out a comprehensive evaluation of diagnostic characters to confirm the lineage D as a distinct species.

Jabuticaba [ Plinia peruviana (Poir.) Govaerts]: a Brazilian fruit with a promising application against itraconazole-susceptible and -resistant Sporothrix brasiliensis - Stefanie Bressan Waller; Cristina Mendes Peter; Jéssica Fernanda Hoffmann; Marlete Brum Cleff; Renata Osório Faria de; João Luiz Zani (Natural Product Research, 2021)

Relevance of Mitochondrial Dysfunction in the Reserpine-Induced Experimental Fibromyalgia Model - Evelyne da Silva Brum; Maria Fernanda Pessano Fialho; Susana Paula Moreira Fischer; Diane Duarte Hartmann; Débora Farina Gonçalves; Rahisa Scussel; Ricardo Andrez Machado-de-Ávila; Cristiane Lenz Dalla Corte; Félix Alexandre Antunes Soares; Sara Marchesan Oliveira (Molecular Neurobiology, 2020)

Overcoming the worst of both worlds: integrating climate change and habitat loss into spatial conservation planning of genetic diversity in the Brazilian Cerrado - José Alexandre Felizola Diniz-Filho; Ana Clara de Oliveira Ferraz Barbosa; Lázaro José Chaves; Kelly da Silva e Souza; Ricardo Dobrovolski; Ludmila Rattis; Levi Carina Terribile; Matheus Souza Lima-Ribeiro; Guilherme de Oliveira; Fernanda Thiesen Brum; Rafael Loyola; Mariana Pires de Campos Telles (Biodiversity and Conservation, 2020)

Evaluating the impact of future actions in minimizing vegetation loss from land conversion in the Brazilian Cerrado under climate change - Lara M. Monteiro; Fernanda Thiesen Brum; Robert L. Pressey; Leonor Patricia C. Morellato; Britaldo Soares-Filho; Matheus S. Lima-Ribeiro; Rafael Loyola (Biodiversity and Conservation, 2020)

Hepatitis A Virus, Hepatitis E Virus, and Rotavirus in Foods of Animal Origin Traded at the Borders of Brazil, Argentina, and Uruguay - Juliano Gonçalves Pereira; Vanessa Mendonça Soares; Fernanda Gil de Souza; Leonardo Ereno Tadielo; Emanoelli Aparecida Rodrigues dos Santos; Mário Celso Sperotto Brum; Andreia Henzel; Eduarda Hallal Duval; Fernando Rosado Spilki; Wladimir Padilha da Silva (Food and Environmental Virology, 2018)

HOE-140, an antagonist of B2 receptor, protects against memory deficits and brain damage induced by moderate lateral fluid percussion injury in mice - Ana Paula Oliveira Ferreira; Fernanda Silva Rodrigues; Iuri Domingues Della-Pace; Bibiana Castagna Mota; Sara Marchesan Oliveira; Camila de Campos Velho Gewehr; Franciane Bobinski; Clarissa Vasconcelos de Oliveira; Juliana Sperotto Brum; Mauro Schneider Oliveira; Ana Flavia Furian; Claudio Severo Lombardo de Barros; et al. (Psychopharmacology, 2014)

Changing precipitation regimes and the water and carbon economies of trees - Rafael S. Oliveira; Bradley O. Christoffersen; Fernanda de V. Barros; Grazielle S. Teodoro; Paulo Bittencourt; Mauro M. Brum-Jr; Ricardo A. G. Viani (Theoretical and Experimental Plant Physiology, 2014)